O horário de estudo docente na Rede Municipal de Educação de Goiânia (2000-2024): análise documental das regulamentações, transformações e contradições - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research, developed within the Academic Master’s Program in Education of the Graduate Program in Education at the State University of Goiás (Inhumas Unit), aims to understand, through documentary analysis, how the Study Hour for teachers in the Municipal Education Network of Goiânia was regulated and represented in legislation and official documents between 2000 and 2024. Framed within the research line Work, State, and Educational Policies, the investigation analyzes the Study Hour as an integral element of teacher appreciation policies, highlighting the movements, continuities, and contradictions that have marked its definition over time, in dialogue with national and local educational policies. The study is guided by the following research question: how has the right to the Study Hour, legally guaranteed to teachers in the Municipal Education Network of Goiânia, been regulated and represented in the network’s official documents, considering the tensions and transformations that have permeated its regulation between 2000 and 2024? The research is based on legal instruments such as the Federal Constitution, the National Education Guidelines and Framework Law, the National Professional Minimum Wage Law, the Political-Pedagogical Proposals, and other municipal regulations. Initially, a bibliographic and documentary review was conducted to systematize the accumulated knowledge on the subject and identify the state of the art, followed by the analysis of official documents. The theoretical framework includes authors such as Antunes (2009), Engels (2006), Formiga (2021), Freire (2016, 2018, 2019), Furtado (2019), Gouveia and Ferraz (2016), Marx (2013), Oliveira (2004, 2007, 2016), Saviani (2007, 2008), among others. With a qualitative approach, the research identifies patterns, trends, and gaps in the policies regulating the Study Hour, highlighting the changes and continuities that have shaped its regulation and emphasizing how these regulations express disputes surrounding teacher appreciation and the organization of the workday in the Municipal Education Network of Goiânia.
Keywords: Carreira docente; Horário de estudo; Jornada de trabalho; Teaching career; Study hour; Workload; CIENCIAS HUMANAS::EDUCACAO